Fiber‐Shaped ZnO/Graphene Schottky Photodetector with Strain Effect. Issue 11 (12th March 2018) - Zhu, Zhengfeng; Wang, Shalong; Zhu, Ying; Liu, Xuhai; Zou, Yousheng; Gu, Yu; Ju, Dan; Zeng, Haibo
Abstract: The flexible fiber‐shaped photodetectors (PDs) suitable for wearable applications have recently attracted enormous research attention. However, the fiber‐shaped structures with the PN junction usually suffer from the poor interface between the all‐inorganic semiconductors and twisted linear electrodes. In this work, fiber‐shaped ZnO/graphene PDs based on a Schottky junction are constructed for the first time. The PDs exhibit excellent device performance because of the combination of the interface and strain engineering. In this novel structure, ZnO nanorod arrays are uniformly grown onto the Zn wire, and a graphene film is wrapped outside as the surface electrode. The built‐in electric field and the conformal contacts facilitate the separation and transport of photoinduced charge carriers. The photoresponsivity is as high as 1.92 A W −1 . Moreover, the device performance can be further improved by applying external compressive strain due to the piezoelectric effect of ZnO. For instance, the responsivity of the PD under −0.33% compressive strain can increase by 12.5% and reach 2.16 A W −1 . Abstract : Fiber‐shaped photodetectors are contructed based on ZnO/graphene Schottky junction to achieve excellent device performance. Together with the built‐in electric field from the Schottky junction, the conformal contacts are in favor of the separation and transport of photoinduced carriers. Moreover, the device performance can be further improved by applying external compressive strain due to the piezoelectronic effect of ZnO.